2018
DOI: 10.1111/exd.13725
|View full text |Cite
|
Sign up to set email alerts
|

Construction of low contracted 3D skin equivalents by genipin cross‐linking

Abstract: Continuous contraction of 3D skin equivalents in construction and use restricts their applications in clinical and pharmaceutical practices. So far, no effective method has been developed to inhibit such contraction. Hence, low cytotoxic cross-linkers, 1-ethyl-3-3-dimethylaminopropylcarbodiimide hydrochloride (EDC) and genipin, are investigated to reduce the contraction in this study. As found, both genipin and EDC at 0.2 and 0.4 mmol/L are nontoxic to collagen-entrapped fibroblasts and upregulate the extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…We used genipin, as the cross-link stabilator of the collagen scaffold for the fibroblast culture. Genipin was also used by Meng and Shen [ 19 ] for the stabilization of collagen for HSE production. The authors observed that 0.4 mmol/L genipin is non-toxic for the fibroblasts and greatly reduces the contraction of 3D skin equivalents from 87% to 28% ( n = 9, p < 0.05) over a 21-day follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…We used genipin, as the cross-link stabilator of the collagen scaffold for the fibroblast culture. Genipin was also used by Meng and Shen [ 19 ] for the stabilization of collagen for HSE production. The authors observed that 0.4 mmol/L genipin is non-toxic for the fibroblasts and greatly reduces the contraction of 3D skin equivalents from 87% to 28% ( n = 9, p < 0.05) over a 21-day follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…3D cell cultures differ greatly from standard 2D cell cultures in cell-cell interactions, cellular mechanics and nutrient access [9]. Briefly, 3D skin equivalents are organotypic culture systems that are generated by seeding human keratinocytes onto a dermal layer with human fibroblasts [10]. The positive trend of increasing acceptance of these models in dermatological research will hopefully lead to a reduction in the number of animals used for experiments to study skin biology, wound healing, skin ageing and disease pathology [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The positive trend of increasing acceptance of these models in dermatological research will hopefully lead to a reduction in the number of animals used for experiments to study skin biology, wound healing, skin ageing and disease pathology [11,12]. In addition, 3D skin equivalents have been developed as an attractive tool for pharmacotoxicological testing of cosmetic components, for clinical applications such as artificial skin grafts and to avoid the need for sequential invasive skin biopsies from patients for standardised studies of human skin [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…The outputs demonstrated similar findings to their previous research; higher swelling in the GNP-crosslinked group (1886 ± 56%) than EDC-crosslinked group (1,658 ± 62%) ( Fauzi et al, 2020 ). The swelling capacity of GNP-crosslinked CH-alginate (ALG)-HA polyelectrolyte composite sponges was monitored by Meng et al (2021) . They saw high swelling for all formulations after 2 h of the experiment (by using low field NMR).…”
Section: Genipin Crosslinking Effect On Biomatrix Propertiesmentioning
confidence: 99%
“…However, TG2-modified films exhibited no significant improvement in mechanical strength at low crosslinking concentration. Another comparison study of GNP and EDC crosslinking has been performed by Meng et al (2018) . They produced 3D skin equivalents from human skin cells and COL gel.…”
Section: Genipin Crosslinking Effect On Biomatrix Propertiesmentioning
confidence: 99%